Single-file diffusion in oxygen underdoped ReBa₂Cu₃O₇₋ₓ (Re=Y, Ho) single crystals - Boiko, Y.I.; Bogdanov, V.V.; Vovk, R.V.; Ort, A.G.; Litvinov, Yu.V. (Functional Materials, 2017)
Analysis of the kinetics of relaxation processes observed at room temperature in the ReBa₂Cu₃O₇₋ₓ (Re=Y, Ho) compounds, having a high-temperature superconductivity is made. It was concluded that the initial (faster) stage of these processes is controlled by a single-file diffusion of oxygen along one-dimensional chains of vacancies, forming in the oxygen sub-lattice of compound with a deficit of oxygen, and final (slow) stage controls by the usual classical diffusion. Presented and discussed the results of two-stage relaxation of the electrical resistance of above mentioned compounds which were a long time (more than three days) at room temperature in air.